The effect of sleep deprivation on objective and subjective measures of facial appearance. (21st April 2019) - Holding, Benjamin C.; Sundelin, Tina; Cairns, Patrick; Perrett, David I.; Axelsson, John
Abstract: The faces of people who are sleep deprived are perceived by others as looking paler, less healthy and less attractive compared to when well rested. However, there is little research using objective measures to investigate sleep‐loss‐related changes in facial appearance. We aimed to assess the effects of sleep deprivation on skin colour, eye openness, mouth curvature and periorbital darkness using objective measures, as well as to replicate previous findings for subjective ratings. We also investigated the extent to which these facial features predicted ratings of fatigue by others and could be used to classify the sleep condition of the person. Subjects ( n  = 181) were randomised to one night of total sleep deprivation or a night of normal sleep (8–9 hr in bed). The following day facial photographs were taken and, in a subset ( n  = 141), skin colour was measured using spectrophotometry. A separate set of participants ( n  = 63) later rated the photographs in terms of health, paleness and fatigue. The photographs were also digitally analysed with respect to eye openness, mouth curvature and periorbital darkness. The results showed that neither sleep deprivation nor the subjects' sleepiness was related to differences in any facial variable. Similarly, there was no difference in subjective ratings between the groups. Decreased skin yellowness, less eye openness, downward mouth curvature and periorbital darkness all predicted increased fatigue ratings by others. However, the combination of appearance variables could not be accurately used to classify sleep condition. These findings have implications for both face‐to‐face and computerised visual assessment of sleep loss and fatigue.